NILAI EKONOMI EKOWISATA MANGROVE DI DESA MARGASARI, KECAMATAN LABUHAN MARINGGAI, KABUPATEN LAMPUNG TIMUR - Ferli Hartati; Rommy Qurniati; Indra Gumay Febryano; Duryat Duryat (Jurnal Belantara, 2021)
The development of mangrove forests as a mean of ecotourism has high economic value. The purpose of this study is to analyze the economic value of mangrove ecotourism. Determination of the sample is using the accidental sampling method. The data are collected by conducting interview and observation techniques in the field, the data will be analyzed descriptively and quantitatively through a travel cost method. The results show that ecotourism visitors come from inside and outside Lampung Province with an average travel cost is Rp 107.500/person/visit. The number of visitors reaches 1.200 people/year, so the economic value generated is Rp 129.000.000/year or Rp 1.038.647/ha/year. The object in the ecotourism location is quite simple, such as in the form of bridges, photo spots, seats, gazebo, and boats to surround the mangrove forest. The government and the community have an important role in the efforts to increase the economic value through the provision of facilities, quality and good services to ensure the sustainability of mangrove ecotourism.